Embedded Economic Behavior in Baatar Jujuran of Banjar Tradition in Banjarmasin - Renny Ismaya; Maman Saputra (West Science Islamic Studies, 2023)
This research delves into the economic behavior embedded in the traditional Banjar wedding process of Baatar Jujuran, a distinctive practice in South Kalimantan, Indonesia. While from a classical economics perspective, individual actions are often viewed as rational and instrumental, this study explores how cultural and religious values significantly influence the economic actions of the Banjar people. This research employs a qualitative approach through in-depth interviews with informants selected via purposive sampling. Three informants were chosen, including a community leader, a cultural expert, and a religious figure with expertise in Islamic perspectives on marriage. Result found Baatar Jujuran involves the groom providing a sum of money to the bride's family, with the amount being determined by the bride, reflecting family social status. Through the theory of embeddedness, this research reveals that economic actions, even in a modern society, remain socially embedded in non-economic institutions like culture and religion, demonstrating the pervasive impact of cultural and religious values. The study also examines the Baatar Jujuran tradition from an Islamic perspective, highlighting its compatibility with Islamic teachings and practices. The findings illustrate how cultural and religious values, along with the dynamics of personal relationships, significantly shape economic behaviors in the Banjar community, offering a unique perspective on economic sociology.